Colloidal Crystals of NaYF4 Upconversion Nanocrystals Studied by Small‐Angle X‐Ray Scattering (SAXS). (3rd December 2018) - Homann, Christian; Bolze, Joerg; Haase, Markus
Abstract: Spherical NaYF4 upconversion nanocrystals with mean radii of about 5 and 11 nm are observed to form colloidal crystals, i.e., 3D assemblies of the particles with long‐range order. The colloidal crystals of the larger particles form directly in solution when dispersions of the particles in toluene are stored at room temperature for several weeks. Crystallization of the smaller particles takes place when their dispersions in hexane are slowly dried at elevated temperatures. The formation and the structure of the colloidal crystals are studied by small‐angle X‐ray scattering (SAXS). SAXS measurements show that the smaller as well as the larger particles assemble into a face‐centered cubic lattice with unit cell dimensions of a = 18.7 nm and a = 35.5 nm, respectively. The SAXS data also show that the particles in the colloidal crystals still bear a layer of oleic acid on their surfaces. The thickness of this layer is 1.5–1.8 nm, as determined by comparing the unit cell dimensions of the colloidal crystals with the mean particle sizes. The latter could be very precisely determined from the distinct oscillations observed in the SAXS data of dilute colloidal dispersions of the nanocrystals. Abstract : Nearly monodisperse NaYF4 upconversion nanoparticles self‐assemble into superlattices also known as colloidal crystals . Small‐angle X‐ray scattering (SAXS) is used to determine the structure of the colloidal crystals and the distances of the particles in these solids, to distinguish amorphous from ordered particle assemblies, and to precisely measure the mean size of the spherical particles in solution.